2013
DOI: 10.1097/gme.0b013e318291f5a6
|View full text |Cite
|
Sign up to set email alerts
|

Objective cognitive performance is related to subjective memory complaints in midlife women with moderate to severe vasomotor symptoms

Abstract: Objective Memory complaints increase as women transition from premenopausal to postmenopausal stages. We explored the extent to which subjective memory complaints were associated with objective cognitive test performance, affective symptoms, and menopausal symptoms in midlife women with moderate to severe vasomotor symptoms. We predicted that subjective memory complaints would be related to affective symptoms and lower performance on tests of memory and attention. Methods Sixty-eight midlife women (mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 43 publications
(56 reference statements)
6
40
0
2
Order By: Relevance
“…Our present findings provide stronger support, albeit tentative given small numbers, of a possible causal relationship between reductions in physiologic VMS and improvements in memory. Changes in memory were unrelated to changes in reported VMS, consistent with previous findings that memory[9] and neuroimaging measures [14, 15] related to physiologic VMS but not reported VMS. Further investigation in larger studies is needed to determine the potential clinical utility of physiologic VMS monitoring to identify women at risk for memory declines.…”
Section: 0 Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our present findings provide stronger support, albeit tentative given small numbers, of a possible causal relationship between reductions in physiologic VMS and improvements in memory. Changes in memory were unrelated to changes in reported VMS, consistent with previous findings that memory[9] and neuroimaging measures [14, 15] related to physiologic VMS but not reported VMS. Further investigation in larger studies is needed to determine the potential clinical utility of physiologic VMS monitoring to identify women at risk for memory declines.…”
Section: 0 Discussionsupporting
confidence: 88%
“…Complaints of forgetfulness correlate with performance on neuropsychological tests of verbal memory, which measure learning and recall of words, stories and other verbal material[9]. Verbal memory worsens during the menopausal transition and after surgical menopause [10-12].…”
Section: 0 Introductionmentioning
confidence: 99%
“…Hot flushes documented subjectively 17 or/and objectively 18 represent the most significant negative predictor of selfreported forgetfulness or retrospective memory functioning [17][18][19] . The severity of hot flushes predicted both the performance in verbal memory scores and the duration of memory problems 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated an association between vasomotor symptoms and memory performance [15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…This decline is particularly apparent on tasks that rely on the dorsolateral prefrontal cortex (dlPFC), such as those that emphasize working memory and cognitive flexibility (Drogos et al, 2013; Weber et al, 2013). The interaction between this loss of estrogens and the risk of decline in cognitive function is not well understood, and studies designed to explore the cognitive benefits of hormone therapy in women have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%